Is Education a Fundamental Right? People's Lay Theories About Intellectual Potential Drive Their Positions on Education. (September 2017) - Savani, Krishna; Rattan, Aneeta; Dweck, Carol S.
Does every child have a fundamental right to receive a high-quality education? We propose that people's beliefs about whether "nearly everyone" or "only some people" have high intellectual potential drive their positions on education. Three studies found that the more people believed that nearly everyone has high potential, the more they viewed education as a fundamental human right. Furthermore, people who viewed education as a fundamental right, in turn (a) were more likely to support the institution of free public education, (b) were more concerned upon learning that students in the country were not performing well academically compared with students in peer nations, and (c) were more likely to support redistributing educational funds more equitably across wealthier and poorer school districts. The studies show that people's beliefs about intellectual potential can influence their positions on education, which can affect the future quality of life for countless students.